HUBUNGAN PERILAKU SELF-MANAGEMENT DENGAN KUALITAS HIDUP PENDERITA HIPERTENSI DI PUSKESMAS MADURAN LAMONGAN - Soliha, Siti; Lestari, Trijati Puspita; Maghfiroh, Isni Lailatul (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p14, 2023)
Increased blood pressure in people with hypertension will have an impact on decreasing quality of life. One of the efforts to prevent complications of hypertension is the application of self-management behavior. People with hypertension have good self-control if they are actively involved in caring behavior and making decisions that support their own health. The purpose of this study was to determine the relationship between self-management behavior and the quality of life of hypertensive patients at the Maduran Lamongan Health Center. This study used a cross-sectional approach to 88 hypertensive patientswho were recruited by consecutive sampling. Data were collected using a questionnaire on hypertension self-management behavior and the quality of life of hypertension sufferers and analyzed using the Spearman Rank test. The results showed that (89,8%) hypertensive patients had self-management behavior. The good one (87,5%) had a good quality of life. The results of the Spearman Rank test showed p = 0,000 (p < 0,05) and r = 0,914 which means that there is a significant relationship between self-management behavior and the quality of life of hypertensive patients with a very strong affinity. Hypertension sufferers who have good self-management behavior will have a high quality of life. Therefore, it is hoped that hypertension sufferers can improve self-management behavior by adopting a healthy lifestyle and routinely monitoring blood pressure at health facilities to achieve the desired quality of life want.